Household characteristics of persons with complex care needs in the community: A preliminary study - Kyoko Yoshioka‐Maeda; Hitoshi Fujii (Wiley, 2021)
Abstract Aim To identify the characteristics of households of persons with complex care needs and clarify the care period length required to resolve their primary health issues. Design A descriptive cross‐sectional study design. Methods We collected registered data and nursing records from 155 households living in City A within the Tokyo Metropolis. They were designated as complex care cases by the home care and life support centre and needed a multidisciplinary approach to care from April 2018-July 2019. Results Most households comprised an elderly with a single adult child (N = 47, 30.3%). Mental illness and economic distress overlapped as the most common issues. The mean length of care period was 147.7 days (SD = 120.6). The log‐rank test showed that single persons took significantly less time to resolve their primary health issues than elders with single‐child households or single‐person <65‐year‐old households.